Building sustainable settlements in Chimoio, Mozambique : the sustainability of using unfired adobe bricks to construct shelter - Savaio, Dieter Santos (Stellenbosch : University of Stellenbosch, 2010)
Thesis ((MPhil (Sustainable Development Planning and Management))--University of Stellenbosch, 2010.